2016
DOI: 10.1038/cr.2016.88
|View full text |Cite
|
Sign up to set email alerts
|

Type V CRISPR-Cas Cpf1 endonuclease employs a unique mechanism for crRNA-mediated target DNA recognition

Abstract: CRISPR-Cas9 and CRISPR-Cpf1 systems have been successfully harnessed for genome editing. In the CRIS-PR-Cas9 system, the preordered A-form RNA seed sequence and preformed protein PAM-interacting cleft are essential for Cas9 to form a DNA recognition-competent structure. Whether the CRISPR-Cpf1 system employs a similar mechanism for target DNA recognition remains unclear. Here, we have determined the crystal structure of Acidaminococcus sp. Cpf1 (AsCpf1) in complex with crRNA and target DNA. Structural comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
194
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(214 citation statements)
references
References 37 publications
8
194
1
Order By: Relevance
“…These structural rearrangements are consistent with a previous prediction, based on a comparison of the LbCpf1 binary complex with the AsCpf1 ternary complex (Gao et al, 2016). As compared to the binary complex, the REC1 and REC2 domains move toward and away from the NUC lobe in the ternary complex, respectively, to form the central channel that accommodates the crRNA-target DNA heteroduplex (Figures 3A, 3B and S3B).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These structural rearrangements are consistent with a previous prediction, based on a comparison of the LbCpf1 binary complex with the AsCpf1 ternary complex (Gao et al, 2016). As compared to the binary complex, the REC1 and REC2 domains move toward and away from the NUC lobe in the ternary complex, respectively, to form the central channel that accommodates the crRNA-target DNA heteroduplex (Figures 3A, 3B and S3B).…”
Section: Resultssupporting
confidence: 92%
“…Previous structural studies provided mechanistic insights into the crRNA-guided DNA recognition and cleavage by the Cpf1 family nucleases (Dong et al, 2016; Yamano et al, 2016; Gao et al, 2016). The crystal structures of the LbCpf1-crRNA binary complex (Dong et al, 2016) and the AsCpf1-crRNA-target DNA ternary complex (Yamano et al, 2016; Gao et al, 2016) revealed the bilobed architectures of Cpf1 and the crRNA recognition mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cfp1 is not homologous to the commonly used CRISPR nuclease, Cas9 and employs a mechanism that is different from that of Cas917. As such, there are several major differences between cas9 and cpf1 systems.…”
mentioning
confidence: 99%
“…Based on the similarity of domain organization, effectors associated with these five sub-types have been classified as variants of the Cas12 family. Only Cas12a (formerly Cpf1) and Cas12b (formerly C2c1) have been extensively characterized both structurally and functionally (Dong et al, 2016; Gao et al, 2016; Liu et al, 2017a; Shmakov et al, 2015; Stella et al, 2017; Swarts et al, 2017b; Wu et al, 2017; Yamano et al, 2016; Yang et al, 2016; Zetsche et al, 2015). Two additional Type V effectors, Cas12d (formerly CasY) and the compact 980 amino acid Cas12e (formerly CasX), have demonstrated RNA-dependent DNA interference activity in in vivo studies (Burstein et al, 2017), while activity of Cas12c (formerly C2c3) has not been established (Shmakov et al, 2015).…”
Section: Type V Crispr-cas Systemsmentioning
confidence: 99%